The Slavic NBN Founder Mutation: A Role for Reproductive Fitness? - Seemanova, Eva; Varon, Raymonda; Vejvalka, Jan; Jarolim, Petr; Seeman, Pavel; Chrzanowska, Krystyna H.; Digweed, Martin; Resnick, Igor; Kremensky, Ivo; Saar, Kathrin; Hoffmann, Katrin; Dutrannoy, Veronique; et al. (PLoS ONE, 2016)
The vast majority of patients with Nijmegen Breakage Syndrome (NBS) are of Slavic origin and carry a deleterious deletion (c.657del5; rs587776650) in the NBN gene on chromosome 8q21. This mutation is essentially confined to Slavic populations and may thus be considered a Slavic founder mutation. Notably, not a single parenthood of a homozygous c.657del5 carrier has been reported to date, while heterozygous carriers do reproduce but have an increased cancer risk. These observations seem to conflict with the considerable carrier frequency of c.657del5 of 0.5% to 1% as observed in different Slavic populations because deleterious mutations would be eliminated quite rapidly by purifying selection. Therefore, we propose that heterozygous c.657del5 carriers have increased reproductive success, i.e., that the mutation confers heterozygote advantage. In fact, in our cohort study of the reproductive history of 24 NBS pedigrees from the Czech Republic, we observed that female carriers gave birth to more children on average than female non-carriers, while no such reproductive differences were observed for males. We also estimate that c.657del5 likely occurred less than 300 generations ago, thus supporting the view that the original mutation predated the historic split and subsequent spread of the 'Slavic people'. We surmise that the higher fertility of female c.657del5 carriers reflects a lower miscarriage rate in these women, thereby reflecting the role of the NBN gene product, nibrin, in the repair of DNA double strand breaks and their processing in immune gene rearrangements, telomere maintenance, and meiotic recombination, akin to the previously described role of the DNA repair genes BRCA1 and BRCA2.
EVALuna2:9351